Inhibition of FOXO1 by small interfering RNA enhances proliferation and inhibits apoptosis of papillary thyroid carcinoma cells via Akt/FOXO1/Bim pathway - Song, Hong-ming (Onco Targets Ther, 2015)
Forkhead box protein O1 (FOXO1) is a multifunctional transcription factor of the forkhead family. It may function as a tumor suppressor through its ability to regulate cellular events, including cell proliferation, apoptosis, and cell cycle control. As reported, FOXO1 is downregulated in papillary thyroid carcinoma (PTC). However, the function of FOXO1 in human PTC remains unclear. In this study, we investigated the function and underlying regulatory mechanisms of FOXO1 in PTC cells. PTC cell lines K1 and TPC1 were transiently transfected with FOXO1 small interfering RNA (siRNA) and negative control RNA. Successful transfection was confirmed by RT-qPCR and Western blot analysis. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell proliferation assays, colony formation assays, apoptosis, and cell cycle assays were used to explore the potential function of FOXO1 in the PTC cell lines. We found that downregulation of FOXO1 promoted cellular proliferation, enhanced clonogenesis, and inhibited cellular apoptosis. However, the cell cycle was not markedly affected by FOXO1 siRNA. Furthermore, Bim, a downstream target of the Akt/FOXO1 signaling pathway, was downregulated at both mRNA and protein levels in cells transfected with FOXO1 siRNA. Collectively, these results indicate that FOXO1 may play an important role in inhibiting PTC development by regulating cellular proliferation, growth, and apoptosis. FOXO1 expression is a potentially useful biomarker for human PTC. Moreover, tumorigenesis of PTC may be associated with repression of the Akt/FOXO1/Bim signaling pathway.